Risk Mitigation Weather Anomaly Impact on PT. XYZ Pure Farming - Nugroho S, Purwoko; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
XYZ pure farming is a pilot project from PT. XYZ Holding as a new business unit who operates in agricultural product. In year 2010 and 2011, the weather anomaly makes some rice plantation failed to harvest or damaged and decrease the amount of production. XYZ pure farming calculate its Earning at risk using three forecasted period gives different risk exposure and use confidence level of 95%. It shows that XYZ pure farming could loss 214 million rupiah in 3 years forecast, increasing to 1.2 billion rupiah in 5 years forecast, and 6.7 billion rupiah at 10 years forecast. Risk management of weather anomaly in XYZ pure farming can be begin with identification of risk based on their type. There are several risk that has been identified such as : Environmental Risk, Counter-party Risk, Operational Risk, Market Risk, and Financial Risk. After risk identification, all risk is scaled based on its severity and probability and then make the risk mapping to helps in problem solving. There are several risk in XYZ pure farming that increase when the rice production is decrease due to the weather anomaly impact. After measure the risk and prioritize the risk, the next step is to mitigate the risk, take an action for the every risk measured. Risk can be mitigated by doing 4 optional actions related to the severity and the probability of the risk itself. There are Retain, Control, Tranfer, and Avoid. Some of XYZ pure farming mitigation action: Capital raising, below the line marketing, new supplier, contact improvement safety stock, smart pricing, partnership program, FiFo System, vacuum sealed package, green house technology R&D in new type of seed, and integrated irrigation system. Keywords: risk management, weather anomaly, SRI, pure farming, return at risk.